Association of sex and aspirin use with postoperative bleeding in patients with lower extremity long bone fractures - Michael Fisher; Kristin Salottolo; David Bar-Or; Matthew Carrick; Kaysie L Banton; Robert Madayag; Chad M Corrigan (Trauma Surgery & Acute Care Open)
Objective The perioperative management of patients on antiplatelet drugs is a rising challenge in orthopedic trauma because antiplatelet drugs are frequently encountered and carry an increased risk of hemorrhagic consequences. The study objective was to examine the effect of aspirin on bleeding outcomes for patients with lower extremity fractures.Methods This retrospective study included patients requiring surgical fixation of traumatic hip, femur, and tibia fractures from January 1, 2018, to March 1, 2020. Patients were excluded if they had a significant head injury, were on chronic anticoagulant therapy, or they did not receive venous thromboembolism chemoprophylaxis. Comparisons between aspirin users (patients on aspirin therapy preinjury) and non-aspirin users were examined using χ2 tests, Cochran-Mantel-Haenszel tests, and multivariate logistic regression. The primary outcome was an overt, actionable bleed (eg, blood transfusion for surgical site hemorrhage) within 24 hours postoperative.Results There were 864 patients with lower extremity long bone fractures and 24% were aspirin users. The incidence of postoperative bleeding was 8.8% and significantly differed for patients taking aspirin versus not (13.6% vs 7.3%, p=0.01). However, biological sex at birth (M/F) was a significant effect modifier (interaction p=0.04). Among women, there were significantly more postoperative bleeds for aspirin users (17.8% aspirin vs 7.4% no aspirin, adjusted OR (AOR): 2.48 (1.28–4.81), p=0.01). Among men, there were similar postoperative bleeding events by aspirin use (5.6% aspirin vs 7.2% no aspirin, AOR: 0.50 (0.14–1.82), p=0.30). Postoperative hemoglobin values <8 g/dL were more frequent among female aspirin users (21.5% aspirin vs 12.5% no aspirin, p=0.01), but this association was not observed in men (p=0.43).Conclusion Women taking aspirin who suffer lower extremity fractures have greater than twofold greater odds of a postoperative bleeding event. These findings suggest adequate perioperative planning to ensure blood availability, and increased awareness to monitor closely for hemorrhage in the 24-hour postoperative window for women taking aspirin preinjury.Level of evidence IV